Activated carbon derived from carbon residue from biomass gasification and its application for dye adsorption: Kinetics, isotherms and thermodynamic studies. (January 2016) - Maneerung, Thawatchai; Liew, Johan; Dai, Yanjun; Kawi, Sibudjing; Chong, Clive; Wang, Chi-Hwa
Graphical abstract: Highlights: Activated carbon (AC) was developed from char via steam activation. AC has high surface area and abundance of hydroxyl and carboxyl groups. AC derived from char exhibited high adsorption capability of dye. AC has a maximum monolayer adsorption capability of 189.83 mg/g. Abstract: In this work, activated carbon (AC) as an effective and low-cost adsorbent was successfully prepared from carbon residue (or char, one of the by-products from woody biomass gasification) via physical activation. The surface area of char was significantly increased from 172.24 to 776.46 m 2 /g after steam activation at 900 °C. The obtained activated carbons were then employed for the adsorption of dye (Rhodamine B) and it was found that activated carbon obtained from steam activation exhibited the highest adsorption capability, which is mainly attributed to the higher surface area and the abundance of hydroxyl (–OH) and carboxyl (–COOH) groups on the activated carbon surface. Moreover, it was also found that the adsorption capability significantly increased under the basic condition, which can be attributed to the increased electrostatic interaction between the deprotonated (negatively charged) activated carbon and dye molecules. Furthermore, the equilibrium data were fitted into different adsorption isotherms and found to fit well with Langmuir model (indicating that dye molecules form monolayer coverage on activated carbon) with a maximum monolayer adsorption capability of 189.83 mg/g, whereas the adsorption kinetics followed the pseudo-second-order kinetics.